Corporate Real Estate Alignment - Monique Arkesteijn (A+BE: Architecture and the Built Environment)
This dissertation aims to enhance CRE alignment by approaching alignment as a design and decision process as is explained in chapter 1. The current state of the art in CRE alignment modeling is summarized in paragraph 2.1. This sets the context of this research and will show that CRE alignment is complex and multidimensional. Thereafter, an assessment of CRE alignment models from a design and decision perspective is made in paragraph 2.2. Based on this perspective I identified the scientific gap of this PhD research. Most of the work in this chapter has been published before in the last 10 years. Figure 2.1 shows the timeline of the important publications related to the two topics that this chapter addresses: